Instrumental Variable Estimates of the Labor Market Spillover Effects of Welfare Reform - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2002)
By increasing the labor supply of welfare recipients, welfare reform may reduce wages and increase unemployment among other less-educated groups. These "spillover effects" are difficult to estimate because welfare caseloads decrease in response to improvements in the economy, which leads caseload reductions to be associated with improvements in labor market outcomes. This paper corrects for the endogeneity of caseloads by using instruments that reflect policy. The estimates suggest that welfare reform has significant spillover effects: welfare reform reduces employment of male high school dropouts, and reduces wages of single mothers and male high school dropouts.
Keywords: J68; J38; I38; J31; H53; 330; welfare; reform; spillover; effects; wages; employment; Bartik